Clinical outcome and outcome prediction of octogenarians with acute basilar artery occlusion and endovascular stroke treatment compared to younger patients - Weyland, Charlotte S.; Mutke, Matthias Anthony; Zimmermann-Miotk, Amanda; Schmitt, Niclas; Chen, Min; Schönenberger, Silvia; Möhlenbruch, Markus Alfred; Bendszus, Martin; Jesser, Jessica (Frontiers in neurology, 2023)
Background and aimsOctogenarians are underrepresented in recently published studies that showed the benefit of endovascular stroke treatment (EST) for patients with acute basilar artery occlusion (BAO). We aimed to compare the clinical outcome of octogenarians with BAO and EST compared to younger patients (YPs) and identify independent outcome predictors.MethodsThis is a retrospective, single-center analysis of patients treated for BAO with EST from January 2013 until June 2021 in a tertiary stroke center. Octogenarians (80-89 years) were compared to YPs. A study endpoint was a favorable clinical outcome as per the modified Rankin Scale (mRS 0-3), 90 days after stroke onset. The study groups were compared using univariate analysis, and a multivariable logistic regression analysis was performed to define independent predictors for favorable and unfavorable (mRS 5-6) clinical outcomes.ResultsIn this study cohort, 74/191 (38.7%) octogenarians had a higher pre-stroke mRS [median, interquartile range (IQR): 2, 1-3 octogenarians vs. 0, 0-1 YP, p < 0.001] and a comparable National Institutes of Health Stroke Scale (NIHSS) before EST (median, IQR: 21, 10-38 vs. 20, 8-35 in YP, p = 0.487). They showed a comparable rate of favorable outcome (mRS 0-3, 90 days, 23.0 vs. 25.6% in YP, p = 0.725), but were less often functionally independent (mRS 0-2: 10.8% in octogenarians vs. 23.0% in YP, p = 0.049). The rate of unfavorable clinical outcome was comparable (mRS 5-6, n = 40, 54.1% in octogenarians vs. n = 64, 54.7% in YP, p = 0.831). A baseline NIHSS was an independent predictor for clinical outcome in YPs [e.g., for unfavorable clinical outcome: odds ratio (OR) 1.061, confidence interval (CI) 1.027-1.098, p = 0.005] and for favorable clinical outcome in octogenarians. Pre-stroke mRS predicted favorable outcomes in octogenarians (OR 0.54, CI 0.30-0.90, p = 0.0291), while age predicted unfavorable outcomes in YPs (OR 1.045, CI 1.011-1.086, p = 0.0137).ConclusionOctogenarians with acute BAO eligible for EST are as likely to achieve a favorable outcome as YPs, and the rate of death or severe disability is comparable. The admission NIHSS is an independent predictor for favorable and unfavorable outcomes in YP and for favorable outcomes in octogenarians. In this study cohort, pre-stroke mRS predicted favorable outcomes in octogenarians while age predicted an unfavorable outcome in YPs.
Gesehen am 26.02.2024